Air-Sea CO2 Exchange in the Strait of Gibraltar - Curbelo-Hernández, David; Santana-Casiano, J. Magdalena; González, Aridane González; González-Dávila, Melchor (Frontiers in Marine Science, 2021)
The seasonal and spatial variability of the CO2 system and air-sea fluxes were studied in surface waters of the Strait of Gibraltar between February 2019 and March 2021. High-resolution data was collected by a surface ocean observation platform aboard a volunteer observing ship. The CO2 system was strongly influenced by temperature and salinity fluctuations forced by the seasonal and spatial variability in the depth of the Atlantic-Mediterranean Interface layer and by the tidal and wind-induced upwelling. The changes in seawater CO2 fugacity (fCO2,sw) and fluxes were mainly driven by temperature despite the significant influence of non-thermal processes in the southernmost part. The thermal to non-thermal effect ratio (T/B) reached maximum values in the northern section (>1.8) and minimum values in the southern section (<1.30). The fCO2,sw increased with temperature by 9.02 ± 1.99 µatm ºC-1 (r2=0.86 and ρ=0.93) and 4.51 ± 1.66 µatm ºC-1 (r2=0.48 and ρ=0.69) in the northern and southern sections, respectively. The annual cycle of total inorganic carbon normalized to a constant salinity of 36.7 (NCT) was assessed. Net community production processes described 93.5-95.6% of the total NCT change, while air-sea exchange and horizontal and vertical advection accounted for <4.6%. The fCO2,sw in the Strait of Gibraltar since 1999 has been fitted to an equation with an interannual trend of 2.35 ± 0.06 µatm yr-1 and a standard error of estimate of ±12.8 µatm. The seasonality of the air-sea CO2 fluxes reported the behaviour as a strong CO2 sink during the cold months and as a weak CO2 source during the warm months. Both the northern and the southern sections acted as a net CO2 sink of -0.82 and -1.01 mol C m-2 yr-1, respectively. The calculated average CO2 flux for the entire area was -7.12 Gg CO2 yr-1 (-1.94 Gg C yr-1).